Faktor-Faktor yang Memengaruhi Keputusan Pembelian Minyak Goreng Kemasan Bermerek di Kota Bandung - Singgih, Saskia Firmani; Utami, Hesty Nurul (Universitas Galuh, 2024)
Consumer behavior influences the purchase decision-making process. The consumer decision process in buying branded packaged cooking oil products will be decided by various things, including product attributes. The purpose of this study is to see how much influence product attributes (brand, product quality, and price) on consumer decisions in buying branded packaged cooking oil in Bandung City. This study uses a quantitative research design with survey methods conducted in three sub-districts, namely Buah Batu District, Babakan Ciparay District, and Bandung Kulon District. The analysis used is descriptive analysis and inferential analysis consisting of regression analysis, T test, and F test. The results showed that product attributes which include brand variables, product quality, and price were only product quality variables that had a negative effect or hypotheses were rejected against purchasing decisions, while brand and price variables had a positive effect. This shows that the majority of consumers making purchases do not make quality the main goal. Consumers make purchases as an obligation to meet basic needs.